Erenumab in Chronic Migraine Patients Who Previously Failed Five First-Line Oral Prophylactics and OnabotulinumtoxinA: A Dual-Center Retrospective Observational Study - Raffaelli, Bianca; Kalantzis, Rea; Mecklenburg, Jasper; Overeem, Lucas Hendrik; Neeb, Lars; Gendolla, Astrid; Reuter, Uwe (Frontiers in Neurology, 2020)
Background: German authorities reimburse migraine prevention with erenumab only in patients who previously did not have therapeutic success with at least five oral prophylactics or have contraindications to such. In this real-world analysis, we assessed treatment response to erenumab in patients with chronic migraine (CM) who failed five oral prophylactics and, in addition, onabotulinumtoxinA (BoNTA). Methods: We analyzed retrospective data of 139 CM patients with at least one injection of erenumab from two German headache centers. Patients previously did not respond sufficiently or had contraindications to β-blockers, flunarizine, topiramate, amitriptyline, valproate, and BoNTA. Primary endpoint of this analysis was the mean change in monthly headache days from the 4-weeks baseline period over the course of a 12-weeks erenumab therapy. Secondary endpoints were changes in monthly migraine days, days with severe headache, days with acute headache medication, and triptan intake in the treatment period. Results: Erenumab (starting dose 70 mg) led to a reduction of −3.7 (95% CI 2.4–5.1) monthly headache days after the first treatment and −4.7 (95% CI 2.9–6.5) after three treatment cycles (p < 0.001 for both). All secondary endpoint parameters were reduced over time. Half of patients (51.11%) had a >30% reduction of monthly headache days in weeks 9–12. Only 4.3% of the patients terminated erenumab treatment due to side effects. Conclusion: In this treatment-refractory CM population, erenumab showed efficacy in a real-world setting similar to data from clinical trials. Tolerability was good, and no safety issues emerged. Erenumabis is a treatment option for CM patients who failed all first-line preventives in addition to BoNTA.